Faktor Penyebab Rendahnya Jumlah Pria dalam Mendukung Penggunaan Alat Kontrasepsi - Subair, Nurlina; Haris, Risma; Nur, Syahban (UNM Environmental Journals, 2018)
This study aims to determine the factors that cause the low number of men who support the use of contraception in order to improve the quality of family welfare. This quantitative descriptive research method was analyzed descriptively on 86 respondents who were observed and interviewed clinically to obtain data on the factors causing the low number of men who supported the use of contraception. The results of the study revealed that from 86 respondents, according to his knowledge that men who did not use contraception with good knowledge were 25 people (29%), men who did not use contraception with enough knowledge were 44 people (51%), and men who did not use the tools contraception with less knowledge as many as 18 people (20%). According to the attitude there are 28 (32%) who agree and 43 people (49%) who disagree, this can be concluded that men assess the use of contraception is very necessary, but not a few of the men who do not agree. This was triggered because of the inherent paradigm that the use of contraceptives was only too long for women.